Tangled times [large type] - Brown, Irene Bennett (Brown, Irene Bennett. Nickel Hill series, 2021)
"In 1901 Kansas, newlyweds Jocelyn and Pete Pladson are determined to make Nickel Hill Ranch a successful cattle operation. For that to happen they must stop cattle rustlers who constantly plague their herd, defy a crazed woman with murder in her eye, and fight fire. A decision about two homeless youngsters who've landed on their doorstep and into their hearts is the easy part"--